Effect of size, color and height of pheromone baited sticky traps on captures of Dacus oleae flies - Haniotakis, G.E. (ENTOMOLOGIA HELLENICA, 1986)
The size of sticky pheromone traps has no effect on Dacus οleae catches when insect population densities are low. At high population densities trap catches increase with surface area. There were no differences in the numbers of D. οleae caught on yellow and white pheromone traps in periods of high pheromone effectiveness, which coincide with periods of high insect reproductive activity. During periods of reduced pheromone effectiveness, due either to low temperatures at the time of pheromone activity (dusk) or reduced insect reproductive activity, traps of yellow hues tend to capture more insects than traps of white color. The height at which pheromone traps are located inside the tree canopy has no effect on catches of D. οleae.